Spatial, seasonal variation and impacts of anthropogenic factors on insect assemblages (Arthropoda: Insecta) in Northwest Morocco - HANAE EL HARCHE; SARA EL HASSOUNI; MOHAMED FADLI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract., El Harche H, El Hassouni S, Fadli M. 2023. Spatial, seasonal variation and impacts of anthropogenic factors on insect assemblages (Arthropoda: Insecta) in Northwest Morocco. Biodiversitas 24: 5368-5375. Agriculture has been identified as one of the main causes of biodiversity loss due to the vast area dedicated to this activity. In Morocco, agroecosystems are becoming increasingly developed, which makes it necessary to study their impact on the local entomofauna. We studied the influence of seasonality and anthropogenic activities, including habitat type, on insect diversity in northwestern Morocco. The insects were collected between March 2019 and February 2020, covering all seasons, using three sampling techniques (sweep nets, pitfall traps, and sight hunting). Our study revealed the presence of 83 species, which were classified into 7 orders belonging to 32 families. Our findings demonstrate that insects diversity changes with the seasons, being higher in spring and summer than in autumn and winter. In addition, insect richness varies according to habitat type, with heterogeneous fields showing greater diversity than homogeneous ones. Research also indicates that anthropogenic pressures have had a detrimental impact on insect diversity, particularly in agricultural activities such as grazing, tillage, and the widespread use of pesticides. The results of this study are essential for the effective conservation and management of insect species worldwide. Accordingly, we make several recommendations to help preserve insect diversity and improve their survival, including reducing the massive use of pesticides and contributing to the global effort to reduce the impacts of climate change, which will not be possible without the cooperation of landowners, farmers, managers, and researchers. Therefore, we can enhance effective conservation and ensure insect species' long-term survival by fostering collaboration and knowledge-sharing among these groups.